Drug-related problems of patients with cardiovascular diseases on hospital admission - Draganov, Ivana; Drndarević, Aneta; Miljković, Branislava; Davidović, Aleksandar; Cvijanović, Dane; Savković, Tatjana; Vezmar Kovačević, Sandra (Archives of Pharmacy, 2022)
In patients with cardiovascular diseases drug-related problems (DRPs) can be associated with hospitalization or rehospitalization. The aim of the research was to analyse DRPs in the cardiology department on admission to the hospital. All patient records on admission to the cardiology department of the Clinical Hospital Center Zvezdara during 2018., were analyzed. Demographic and treatment data of the patient before admission to the hospital were collected. DRPs associated with pre-hospital treatment were identified and classified according to the PCNE (Pharmaceutical Care Network Europe, version 9.1) classification. DRPs were also evaluated as cause of the patient’s hospitalization. Data were analyzed descriptively and with linear regression analysis. During the research period, 143 patients were admitted to the cardiology department, with an average age of 69.75 ± 10.11 years, of which 65.7% were male. Patients had an average of 4.36±2.13 diagnoses and 5.24±3.39 medications on admission. We observed 1.85±1.37 DRPs per patient (range 0-5). The most common DRP (75.6%) was lack of ≥1 drugs in the therapy preceding the admission, most often statins (30.1% of patients), beta-blockers (25.9%), angiotensin-converting enzyme inhibitors (17.5%) and antiarrhythmics/anticoagulants (12.6%). In 96 patients (67.1%) the identified DRPs could be associated with the cause of hospitalization. Atrial fibrillation was the predictor of the number of DRPs in patients (p <0.001). In most cardiovascular patients, the cause of hospitalization could be associated with DRPs before admission. Incomplete therapy of the patient was commonly observed, the cause of which may be inadequate prescribing or lack of adherence of the patient.